Soil sampling optimization using spatial analysis in irrigated mango fields under brazilian semi-arid conditions - Kátia Araújo da Silva; Marcos Sales Rodrigues; Filipe Bernard Ramos Moreira; Aíris Layanne Ferreira Lira; Augusto Miguel Nascimento Lima; Ítalo Herbert Lucena Cavalcante (Revista Brasileira de Fruticultura, 2020)
Abstract Soil sampling is a fundamental procedure in the decision making regarding the management of the soil, thus, a sampling plan should represent as accurately as possible the evaluated crop field. Therefore, the objectives of this study were to suggest a soil sampling approach and soil sampling point allocation using spatial analyses and compare to the classic statistic method in irrigated mango orchards in the Brazilian semi-arid region. The experiment was carried out in three commercial mango orchards located in the region of the São Francisco Valley, Brazil. Soil samples were collected in 0-0.2 m and 0.2-0.4 m depths following regular grids where the number of samples varied from 50 to 56. Soil texture, soil bulk density, soil total porosity, microporosity, macroporosity, pH, Ca, Mg, Na, K, Al, P, potential acidity, and the sum of basis were evaluated. Classical and geostatistical statistics were used to determine the ideal number of soil samples. Fuzzy c-means clustering technique was used to separate the areas into homogeneous zones and to allocate the sampling points. The wide method of 20 individual soil samples proved to be inefficient. On the other hand, the use of geostatistics proved to be efficient and is required for each crop field. The c-means clustering was adequate to separate the areas into homogeneous zones and, thus, to assist the sampling point allocation.